Relationship between Academic Self-Concept and Construction in Hostel with Independence Students Learning At Al-Islamic Boarding School - Hasibuan, Ummi Kalsum; Daharnis (Department of Guidance and Counseling, FIP, Undiksha, 2024)
This research is motivated by the low level of student learning independence. Academic self-concept and guidance in the dormitory are factors that are thought to influence student learning independence. This study aims to analyze the relationship between academic self-concept and guidance in the dormitory with student learning independence. This study was conducted using a quantitative approach with a descriptive correlational type. The population of this study was 274 students in grades VII, VIII and IX of Al-Yusufiyah Islamic Boarding School and a research sample of 163 students. Sampling used the proportional random sampling technique. The instruments used were instruments on academic self-concept, guidance in the dormitory and learning independence with a Likert scale model. The research data were analyzed using simple regression and multiple regression. The results of the study showed that (1) in general, academic self-concept was in the very high category, (2) guidance in the dormitory was in the very good category, (3) learning independence was in the high category, (4) there was a significant relationship between academic self-concept and learning independence, (5) there was a significant relationship between guidance in the dormitory and learning independence, (6) there was a significant relationship between academic self-concept and guidance in the dormitory together with learning independence. The research results can be used as consideration for compiling guidance and counseling service programs that can optimize students' learning independence.